Pencegahan Pernikahan Dini Dan Peningkatan Minat Melanjutkan Pendidikan Berlandaskan Nilai-Nilai Islam - Kurnia, Agus; Lestari, Nanda; Ratih, Wahyu Erinna; Subiyanto, Resa Putri Fibriyanti; Anggraini, Safira Fitri; Permadi, Sufria Dimi; Wardani, Putri Amalia (Fakultas Ushuluddin, Adab, dan Dakwah, 2024)
Early marriage and low interest in education are still problems in several areas in Indonesia, including the Central Lombok area with a fairly high rate of child marriage, so it has a big impact on the length of schooling and the quality of education in the area. This service aims to prevent child marriage, increase interest in education and strengthen the younger generation at Al-Hananiyah Islamic Middle School, Bodak Hamlet, Central Lombok, West Nusa Tenggara. This service method is carried out by educating peers by providing education about the dangers of early marriage and the importance of education. The results of the service show an increase in students' knowledge about the dangers of early marriage and the importance of education as well as an increase in students' interest in completing their education. The conclusion in this service shows the importance of education for the younger generation, especially regarding future orientation so that they are not fixated on getting married at a young age which has the potential to cause several problems in the future such as poverty, stunting and low human resources which have an impact on human resource development and sustainable development.